Scaffolding learning for independence: Clarifying teacher and teaching assistant roles for children with special educational needs. (April 2015) - Radford, Julie; Bosanquet, Paula; Webster, Rob; Blatchford, Peter
Abstract: Support for children with special educational needs (SEN) in inclusive classrooms, in many countries, continues to be provided by teaching assistants (TAs). Whilst they frequently take responsibility for instruction, they are rarely adequately trained and prepared. As TAs have ample opportunities for individualised and group interactions, this paper recommends scaffolding as the key theory to inform their practice. From a large dataset of interactions in mathematics and literacy lessons, episodes of TA scaffolding were selected. Using conversation analysis, three scaffolding roles emerged: 1) a support role that maintained learner engagement, on-task behaviour and motivation; 2) a repair function that focused on learning and fostered independence when children were in difficulty; and c) a heuristic role that encouraged students to use their own learning strategies. The paper concludes with implications for trainers and managers and how teachers can support TAs in implementing each role. Highlights: In inclusive classrooms support is often provided by untrained teaching assistants. Three TA scaffolding roles are proposed: a) support b) repair and c) heuristic. Extracts of talk show effective implementation of the three scaffolding roles. Implications for the management and training of teaching assistants are discussed.